Prague Soundscapes - Jurková, Zuzana, a, kol (Karolinum, 2014)
Prague Soundscapes is the first book focusing on music in Prague from other than musical-historical perspectives. It approaches musical events in present-day Prague from an ethno-musicological position, sometimes called musical anthropology. We take in, for instance, the Refufest festival, a punk concert at the Modrá vopice club,a performance of Dvořák's Rusalka at the National Theatre or accompany followers of the Hare Krishna and their procession through Prague - not just to see and "hear" their music, but also to learn who makes and listens to it and why. An abundance of photographs accompany the book's text, helping the reader become one of the participants. "Prague Soundscapes is a wonderful book whose content is presented in an original and convincing manner... I feel that this will contribute significantly to the development of a new field of musical anthropology - a field that has up to this point been the home, especially in the USA, of urban ethnomusicology." Speranţa Rădulescu, National University of Music Bucharest
Keywords: Ostatní